Extraction and optimization of phytochemicals from Curcuma xanthorrhiza Roxb. - Azemi, Najiba (2020)
Curcuma xanthorrhiza belongs to the Zingiberaceae family is a rich source of phenolics and terpenoids with various bioactivities. The essential oil from the rhizomes was obtained by hydro-distillation and analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). Xanthorrhizol (1), ar-curcumene (4), and a-cedrene (18) were found as the most abundant constituents in the essential oil. Optimization of the ultrasound-assisted extraction (UAE) of the extract from the rhizomes of C. xanthorrhiza was carried out via response surface methodology (RSM). Seventeen experiments were developed with Box-Behnken design (BBD) using three variables which are extraction time (5, 12.50, 20 min), temperature (30, 40, 50°C), and liquid-solid ratio (6, 8, 10 mL/g), respectively. The effect of parameters on the responses of extraction yield, quantification of xanthorrhizol (1), and curcumin (2) was determined. In the extracts, xanthorrhizol (1) and curcumin (2) were quantified using reversed-phase high-performance liquid chromatography (RP HPLC) combined with a photodiode array detector. The highest percentage of yield (72.20%) and the concentration of xanthorrhizol (1) (85.68% w/w) were found at the extraction temperature of 50°C, time of 20 minutes and 8 mL/g liquid-solid ratio. The highest concentration of curcumin (2) (39.73% w/w) was found at the extraction temperature of 30°C, time of 12.50 minutes, and 10 mL/g liquid-solid ratio. Experimental values are closely agreed with the predicted values. The determination coefficient (R2) of extraction yield, xanthorrhizol (1), and curcumin (2) are 0.9960, 0.9983, and 0.9990, respectively. The variance analysis (ANOVA) showed good quadratic model. The numerical data suggested the success of the RSM method in optimizing the phytochemicals extraction parameters from the rhizomes of C. xanthorrhiza.